Affective subjectivity and queer childhood: An analysis of the movie Wild Tigers I Have Known - Brenes Vargas, Alonso (2022)
This essay proposes a critical analysis of the affective subjectivity of a queer childhood, based on Cam Archer's film Wild Tigers I Have Known. The intention is thus to provide an understanding of how heteronormative violence is imprinted on the affectivity of the «queer child»